Theoretical, Legal and Empirical Aspects of Corporate Governance - Sabău Georgeta Valeria; Dumiter Florin Cornel (Journal of Legal Studies)
The study tackles the problem of corporate governance from three directions. First, it reveals the theoretical aspects of corporate governance, with a special focus on public enterprises and the shift towards the new legislative package. Second, corporate governance is analyzed based on the legislative and legal aspects of public enterprises, which are financed by the state budget, and their implication vis – á – vis of the new legislative amendments and legal developments. Third, it is analyzed from the empirical point of view, the corporate governance indicators at the OECD and the Romanian levels. The conclusions of the study highlight the importance of central and public authorities in the field of corporate governance, which are fundamental in order to apply in a fair and complete manner the legal norms and stipulations.